1999
DOI: 10.1007/s002130050924
|View full text |Cite
|
Sign up to set email alerts
|

Plasma serotonin level after 1 day of fluoxetine treatment: a biological predictor for antidepressant response?

Abstract: These preliminary data show that fluoxetine and norfluoxetine might influence 5-HT peripheral venous blood parameters and that plasma 5-HT after 1 day of treatment might be a biological predictor for antidepressant response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 20 publications
4
36
0
1
Order By: Relevance
“…The effect of SSRIs on plasma serotonin concentrations is not well understood, and published results are contradictory – with some studies reporting decreased plasma serotonin after SSRI treatment 32, 62-65 , while others report increased concentrations 66-69 , which may be due, in part, to the plasma collection method or the platform used to assay serotonin. However, we observed a clear decrease in those concentrations in PGRN-AMPS MDD patients as measured with an LCECA platform – a highly sensitive, quantitative method.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of SSRIs on plasma serotonin concentrations is not well understood, and published results are contradictory – with some studies reporting decreased plasma serotonin after SSRI treatment 32, 62-65 , while others report increased concentrations 66-69 , which may be due, in part, to the plasma collection method or the platform used to assay serotonin. However, we observed a clear decrease in those concentrations in PGRN-AMPS MDD patients as measured with an LCECA platform – a highly sensitive, quantitative method.…”
Section: Discussionmentioning
confidence: 99%
“…The blood 5-HT level after 1 day of fluoxetine (one of the typical selective serotonin reuptake inhibitors (SSRIs)) treatment is correlated to the depression degree (P < 0.05). 15 The treatment of Paroxetine (SSRIs) also has the similar effect. 16 In this study, we built a chronic unpredictable mild stress model (CUMS) on rats which mimicked the depression of people and tried to find the relationship between depression behavior and blood 5-HT level.…”
Section: Introductionmentioning
confidence: 99%
“…Alvarez et al studied the effects of therapy with fluoxetine and clomipramine for 12 weeks. They found both drugs had no difference in effect on the platelet inositol phosphate but the platelet activity was normalized among patients who responded to the antidepressant treatment 36 . In a study of depressed patients with CHD, reduced platelet activity occurred in patients treated with paroxetine for 6 weeks but not in patients treated with nortriptyline.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have indicated that SSRIs reduce elevated platelet activities, which may or may not occur in treatment with other kinds of antidepressants 8, 3638 . Alvarez et al studied the effects of therapy with fluoxetine and clomipramine for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%